Pandangan Remaja Dari Segi Agama Islam Dan Kesehatan Mengenai Pornografi Anak - Helmi Kurniawan; Afida Salsabila (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
In the increasingly widespread internet access in this era of technological development, pornography sites can be easily reached. In this article, we will focus on the study of child pornography. Child pornography is an activity carried out by individuals and groups carried out by watching, sending some letters, taking pictures or videos, storing, spreading vulgar content, and other activities that focus on children. Child pornography can have a very bad impact on the person who carries out its activities as well as for the child who is a victim of the pronography itself. This article will explain the views of Islam and the World of Health about the possible effects of activities related to child pornography. The method we used in making this article uses quantitative methods by distributing questionnaires among teenagers. As for the creation of this article, it is hoped that the Indonesian Child Protection Commission will pay more attention to children who are victims of child pornography and supervise suspicious matters related to child pornography.